1993
DOI: 10.1007/bf01997056
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of varicella thrombophlebitis as a complication of varicella zoster virus infection

Abstract: Three cases of deep venous thrombosis following varicella infection are described which were successfully treated with bed rest and anticoagulants. Two of these patients had severe pulmonary manifestations of varicella and the third was complicated by pulmonary embolism. Deep vein thrombosis is an uncommon systemic manifestation of varicella, possibly associated with vascular endothelium wall damage caused by varicella zoster virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Other complications may occur in immunocompetent adults including hepatitis, glomerulonephritis, encephalitis, and meningitis. Thrombotic complications have been reported in adults [23] and in children; 6 cases with thromboses were associated with deficient levels ofprotein coagulation inhibitors [24].…”
Section: Host Relationships Of Vzvmentioning
confidence: 99%
“…Other complications may occur in immunocompetent adults including hepatitis, glomerulonephritis, encephalitis, and meningitis. Thrombotic complications have been reported in adults [23] and in children; 6 cases with thromboses were associated with deficient levels ofprotein coagulation inhibitors [24].…”
Section: Host Relationships Of Vzvmentioning
confidence: 99%
“…Furthermore, transient protein S de®-ciency due to the presence of an antiprotein S antibody seems to be the major cause of this complication [8,9,10,11,12]. Manco-Johnson et al recently reported the association of thrombosis with the presence of aPL antibodies in varicella infections in a study investigating the cause of purpura fulminans, disseminated intravascular coagulation, and thrombosis in seven children with varicella [13].…”
Section: Discussionmentioning
confidence: 95%
“…Venous thrombosis with bilateral digital gangrene, in absence of disseminated intravascular coagulation, has been described after chickenpox in a 6-year-old child by Gyde et al [13]. Gogos et al [14] described three cases of varicella thrombophlebitis and considered it as an uncommon systemic manifestation of varicellazoster viral infection. Of these, two cases had severe pulmonary manifestations of varicella and the third case had pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%